Use of lipid encapsulated tannin to replace ionophore in mitigating enteric methane emission and manipulating dietary protein bypass in SA mutton merino sheep - Hassen, Abubeker (University of Pretoria, 2024)
Thesis (PhD (Animal Science))--University of Pretoria, 2024.